2011
DOI: 10.1016/s1674-8301(11)60024-9
|View full text |Cite
|
Sign up to set email alerts
|

Crystalloid and colloid preload for maintaining cardiac output in elderly patients undergoing total hip replacement under spinal anesthesia

Abstract: The aim of the present study was to compare the effects of colloid and crystalloid preload on cardiac output (CO) and incidence of hypotension in elderly patients under spinal anesthesia (SA). A randomized, double-blinded study was conducted including 47 elderly patients undergoing scheduled total hip replacement (THR), who were randomized to three groups: the control group (C group, n = 15), crystalloid (RS group, n =16) and colloid group (HES group, n = 16). An intravenous preload of 8 mL/kg of either lactat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…Studies also focus on the importance of intravascular filling and the role of adequate preoperative loading with either colloid or crystalloid. 36 Finally, the present study examined hypotension only during the intraoperative period, from the induction of anaesthesia until onward transfer of the patient's care in the post-anaesthesia care unit.…”
Section: Resultsmentioning
confidence: 99%
“…Studies also focus on the importance of intravascular filling and the role of adequate preoperative loading with either colloid or crystalloid. 36 Finally, the present study examined hypotension only during the intraoperative period, from the induction of anaesthesia until onward transfer of the patient's care in the post-anaesthesia care unit.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies investigated benefit of preload or coload to decrease incidence of post spinal hypotension, Rufeng Xie study suggested that use of moderate volume of colloid preload is more effective than crystalloids in maintaining the CO and hemodynamic stability in elderly patients [25].…”
Section: Discussionmentioning
confidence: 99%
“…Fluid preloading has been associated with less spinal hypotension in elderly patients. 13 However there is a lack of consensus in the literature as to the type of fluid and the amount of fluid needed for preloading prior to induction of spinal anaesthesia. The literature suggests the use of fluid preloading as being protective against the development of spinal hypotension in elderly patients, and colloids more so than crystalloids.…”
Section: Interpretation Of the Studymentioning
confidence: 99%